2013
DOI: 10.4049/jimmunol.1200728
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Identifies MicroRNAs that Associate with Pathogenic Autoimmune Neuroinflammation in Rats

Abstract: MicroRNAs (miRNAs) are known to regulate most biological processes and have been found dysregulated in a variety of diseases, including multiple sclerosis (MS). In this study, we characterized miRNAs that associate with susceptibility to develop experimental autoimmune encephalomyelitis (EAE) in rats, a well-established animal model of MS. Using Illumina next-generation sequencing, we detected 544 miRNAs in the lymph nodes of EAE-susceptible Dark Agouti and EAE-resistant Piebald Virol Glaxo rats during immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 75 publications
5
57
0
2
Order By: Relevance
“…However, the identification of changes in miR‐21 expression in EVs after TBI agrees with increases in whole brain tissue observed by others . Other than TBI, increased expression of miR‐21 has also been observed in many models of neuroinflammation and neuronal injury .…”
Section: Discussionsupporting
confidence: 88%
“…However, the identification of changes in miR‐21 expression in EVs after TBI agrees with increases in whole brain tissue observed by others . Other than TBI, increased expression of miR‐21 has also been observed in many models of neuroinflammation and neuronal injury .…”
Section: Discussionsupporting
confidence: 88%
“…Such reduced threshold of activation of T H 17 cells compared with other T-cell subsets may lead to increased responses to a specific antigen. Of note, miR-181a was recently associated with the susceptibility to develop EAE in rats, showing higher expression in a strain susceptible to EAE compared with an EAE-resistant one 42 , pointing towards a potential role for miR-181a in regulating specific T H 17-cell responses in autoimmunity.…”
Section: Articlementioning
confidence: 99%
“…Bergman et al have demonstrated that the PRKCD gene is a direct target of miR-181a in a rat model of multiple sclerosis. 47 Ke et al and Chen et al found that miR-181a could inhibit the irradiation-and cisplatininduced apoptosis of human squamous cervical carcinoma cells via downregulating the expression levels of PRKCD. 48,49 PBX3 PBX3, a HOXA cofactor gene, can encode pre-B-cell leukemia transcription factor 3, which is capable of regulating the transcription of downstream targets by forming stable heterocomplexes with HOX and MEIS proteins.…”
Section: Protein Kinase C Delta Typementioning
confidence: 99%